Demographic and Obstetric Determinants of Section Cesarean in RSUP Dr. M. Djamil Padang in 2019 - Asy Syukri, Muhammad Hasbi; Desmawati, Desmawati (Fakultas Kedokteran Universitas Andalas, 2023)
Introduction: Demographic and obstetric determinants are the dominant factors for the incidence of section cesarean, such as; age, education, occupation, parity, history of wrong delivery, and obstetric complications. This research aims to determine the determinants of demography and obstetric service section cesarean section at RSUP Dr. M. Djamil Padang in 2019. Method: This type of research is an observational descriptive research design cross-sectional. The form sample is secondary data used in the total sampling method, which comes from 420 mothers maternity. Research in analysis univariate and presented in form table frequency. Results: Research obtained that mothers give birth by section cesarean was a risky parity (59.77%), the most medically indicated was placenta previa (27.27%), and more than half (58.64%) were mothers with a history of abnormal delivery, the majority (80.90%) mothers with higher education. Most (67.73%) of mothers with a section cesarean are in the fertile period or not at risk, and more than half (55.00%) of mothers who receive sectional services cesarean section is a mother who does not work. Conclusion: Implied this research found mother section cesarean age risk, education high, no work, parity risk, and history of labor risk, with the indication of most medical incidents that is placenta previa. Suggestions are that mothers are expected to be able to know from the start what risk factors or abnormal labor are.